Metal-free aminocarbonylation of p-quinone methides with isocyanides: synthesis of sterically hindered alpha-arylated acetamides - Shirsath, Sachin R.; More, Devidas A.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2022)
The synthesis of sterically hindered alpha-arylated acetamides generally requires a multistep reaction sequence and is also difficult to access due to steric constraints. This protocol allows the synthesis of sterically hindered alpha-arylated acetamides in moderate to high yields via 1,6-addition of isocyanides to p-quinone methides in the presence of BF3 center dot OEt2. The present transformation features transition metal-free conditions, avoiding the use of toxic carbon monoxide, broad substrate scope, mild reaction conditions, and operational simplicity.
Keywords: Aminocarbonylation; Isocyanide; p-Quinone methide; Sterically Hindered alpha-Arylated Acetamides